The importance of biotic entrainment for base flow fluvial sediment transport - Rice, Stephen P.; Johnson, Matthew F.; Mathers, Kate; Reeds, Jake; Extence, Chris (American Geophysical Union, 2016)
Sediment transport is regarded as an abiotic process driven by geophysical energy, but zoogeomorphological activity indicates that biological energy can also fuel sediment movements. It is therefore prudent to measure the contribution that biota make to sediment transport, but comparisons of abiotic and biotic sediment flux are rare. For a stream in the UK, the contribution of crayfish bioturbation to suspended sediment flux was compared with the amount of sediment moved by hydraulic forcing. During baseflow periods, biotic fluxes can be isolated because nocturnal crayfish activity drives diel turbidity cycles, such that night-time increases above day-time lows are attributable to sediment suspension by crayfish. On average, crayfish bioturbation contributed at least 36% (430 kg) to monthly baseflow suspended sediment loads; this biotic surcharge added between 4.7 and 13.54 t (0.19 to 0.55 t km-2 yr-1) to the annual sediment yield. As anticipated, most sediment was moved by hydraulic forcing during floods and the biotic contribution from baseflow periods represented between 0.43 and 1.24% of the annual load. Crayfish activity is nonetheless an important impact during baseflow periods and the measured annual contribution may be a conservative estimate because of unusually prolonged flooding during the measurement period. In addition to direct sediment entrainment by bioturbation, crayfish burrowing supplies sediment to the channel for mobilization during floods so that the total biotic effect of crayfish is potentially greater than documented in this study. These results suggest that in rivers, during baseflow periods, bioturbation can entrain significant quantities of fine sediment into suspension with implications for the aquatic ecosystem and baseflow sediment fluxes. Energy from life rather than from elevation can make significant contributions to sediment fluxes.